OPTIMALISASI MASKER PEEL-OFF GEL BUNGA TELANG (Clitoria ternatea L.) BERBASIS ALGINAT-XANTHAN GUM MENGGUNAKAN METODOLOGI PERMUKAAN RESPONSIF - Aurum Dwi Utami; Tubagus Akmal (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
Butterfly pea flowers are proven to contain phenolics and flavonoids, which are natural antioxidants that can be utilized in skincare such as peel-off gel masks. This study aims to obtain the optimal formula of peel-off gel mask preparation with varying concentrations of Sodium Alginate (SA) as a gelling agent, Xanthan Gum (XG) as a viscosity modifier and Propyleneglycol (PG) as a plasticizer. Optimization of the base formula was carried out with Box-behnken Design using Design Expert v.13.0 software with test responses of pH value, viscosity, spreadability, drying time and thickness. The base optimization process was carried out with 15 formulas and the optimization results showed a significant research model with the optimum formula results of 1.5% SA, 1% XG and 10% PG with a desirability value of 0.933. The optimum formula was then made and used as a base for pee-off gel mask formula of butterfly pea extract (BFE). The stability test showed significant differences (p<0.05) for the pH, viscosity, spreadability, and thickness tests. The drying time test showed no significant difference (p>0.05) in the peel-off gel mask formula of BFE against the formula base. The results of all test responses during physical stability testing still meet the gel evaluation criteria.